Leakage detection in pipelines using empirical mode decomposition - Mohd Erman Fairuz, Zaidi (2013)
This thesis deals with leakage detection in pipeline using empirical mode decomposition (EMD). Leakage in pipelines being a major problem in industry that use piping system in their operation, for example water distribution company. The objectives of this thesis are to study the leakage detection method and signal processing method then utilize them to detect and locate the leakage. This thesis describes experimental conduct to visualize usual type of leakage in pipeline system. The experiment was design to have certain part of piping system and leakage is attached to the system. This experimental test rig also attached with pressure transducer at the top of the solenoid valve. Sensor use in this experiment is piezoelectric pressure sensor. The signal was captured with data acquisition component and synchronised with Daisy Lab software. Data then being analyzed with Matlab software. In Matlab software, one of signal processing method; empirical mode decomposition was applied to detect the leakage. Peak show at the graph visualize the present of leak in the pipe system. The location of the peak than be analyse to get the time taken by the signal approaching the leak. This time then being calculated using distance leakage formula given to locate the distance of the leakage from the sensor attached. Then the data is compared with the designed leak so the result can be compared and discussed. The results show the error in conducting the experiment because major from the noise from the pump and recommendation to improve the process of detecting leakage also being includes for further test and experiment such as better design of experiment, other parameter can be use in further experiment and other